Interactive-whiteboard-technology-supported collaborative writing: Writing achievement, metacognitive activities, and co-regulation patterns. (April 2021) - Teng, Mark Feng
Abstract: Interactive whiteboard technology is a helpful tool for learning to write. However, collaborative writing among English language learners using this technology remains underexplored. This study considers the potential effects of collaborative writing supported by interactive whiteboard technology on students' writing performance. A total of 120 students who learned English as a foreign language (EFL) participated in this study. Quantitative results revealed that interactive whiteboard technology integrated with collaborative writing instruction resulted in greater improvement in students' writing performance, followed by traditional whiteboard–integrated collaborative writing and traditional collaborative writing instruction without whiteboard technology. Qualitative results further suggested that the patterns and timing of metacognitive activities varied across the three groups. Learners receiving interactive whiteboard–integrated collaborative writing instruction exhibited higher levels of metacognitive activities and were more engaged in coregulation. Implications for using interactive whiteboard–integrated collaborative writing to promote writing instruction are discussed.